INFLUENCE ON RESULTS AND PRODUCT KNOWLEDGE TOWARDS CUSTOMER INTERESTS IN PRODUCT SELECTION AT KSPPS BAITUL MAAL WAT TAMWIL NAHDLATUL ULAMA EAST JAVA TLOGOSARI BRANCH - Hayati, Erlina; Sholihah, Dawimatus (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
This study aims to analyze and empirically test the variables in the study that have been formulated in the formulation of the problem classified as explanatory research, namely whether there is an influence between profit sharing (X1) and product knowledge (X2) on customer interest (Y). In this study, the approach used is to use a quantitative research method. The sampling technique in this study uses on-probability sampling, while the method used for sampling uses purposive sampling. The sample in this study includes customers of KSPPS Baitul Maal Wat Tamwil (BMT) Nahdlatul Ulama East Java, Tlogosari Branch, both savings and financing members. Data analysis used in this study uses multiple linear regression.